(untitled) (Jurnal Sosial Ekonomi Pertanian, 2026)
Abstract This study aims to examine several factors that are assumed to influence the productivity of oil palm harvest workers at PTPN IV Regional 1, Bangun Estate, Simalungun Regency, including age, years of service, formal education, travel distance, and harvest incentives. A quantitative approach was employed using a saturated sampling technique, involving all 30 harvest workers as the study participants. Primary data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression in SPSS, preceded by validity, reliability, and classical assumption tests. The results indicate that the five independent variables simultaneously and significantly affect workers’ productivity (F = 261.379; Sig. = 0.000), with an Adjusted R² of 0.978, indicating that the model explains 97.8% of the variation in harvest workers’ productivity. Individually, only harvest incentives had a significant effect on productivity (β = 0.560; t = 17.600; t-table = 2.064), whereas age, years of service, travel distance, and formal education did not reach statistical significance. The company is therefore recommended to maintain its performance-based incentive scheme, expand employee skill development programs, and address logistical constraints that may reduce operational efficiency. Keywords: harvest incentives, multiple linear regression, oil palm harvest workers, PTPN IV Regional 1, worker productivity, years of service.